PERBANDINGAN PEMERIKSAAN TINJA ANTARA METODE FLOTASI DAN METODE RITCHIE DALAM MENDETEKSI SOIL TRANSMITTED HELMINTH - Wasilah, Nayla; Sulaeman; Sundara Mulia, Yuliansyah; Firman Solihat, Mohamad (Jurnal Kesehatan Siliwangi, 2024)
Microscopic stool examination has two examinations, namely qualitative and quantitative examination. Methods that can be done for qualitative fecal examination are direct slide method, anal swab method, flotation method, tape method, and sedimentation method. While in quantitative examination, namely Stoll, Ritchie, and Kato Katz. This study aims to determine the difference in the identification results of the number of eggs of each species found in the Flotation Method and the Ritchie Method. This research was conducted at the Parasitology Laboratory of the Polytechnic of the Ministry of Health Bandung in March-April 2024. The population in this study was obtained from feces suspected of Soil Transmitted Helminth. The number of samples used in this study were 30 samples using purposive sampling method, namely sampling techniques with certain criteria. Data analysis used the Paired Sample T Test statistical test by calculating the sensitivity and specificity values. The results showed that the number of Soil Transmitted Helminth eggs was found more in the ritchie method, namely in Ascaris lumbricoides 350 (84.95%) and Trichuris trichiura 62 (15.05%), while in the flotation method in Ascaris lumbricoides 195 (85.15%) and Trichuris trichiura 34 (14.85%). Flotation method and Ritchie method have the same sensitivity and specificity values, namely 100% sensitivity and 0% specificity. The results of the Paired Sample T Test have a significant value of 0.001 (p < 0.05) indicating that there is a difference in the results of STH examination with flotation and ritchie methods.